Phylogenetic analyses of Podaxis specimens from Southern Africa reveal hidden diversity and new insights into associations with termites. Issue 9 (September 2016) - Conlon, Benjamin H.; de Beer, Z. Wilhelm; De Fine Licht, Henrik H.; Aanen, Duur K.; Poulsen, Michael
Abstract: Although frequently found on mounds of the grass-cutting termite genus Trinervitermes, virtually nothing is known about the natural history of the fungal genus Podaxis ( Agaricaceae ) nor why it associates with termite mounds. More than 40 species of this secotioid genus have been described since Linnaeus characterised the first species in 1771. However, taxonomic confusion arose when most of these species were reduced to synonymy with Podaxis pistillaris in 1933. Although a few more species have since been described, the vast majority of specimens worldwide are still treated as P. pistillaris . Using 45 fresh and herbarium specimens from Southern Africa, four from North America and one each from Ethiopia, and Kenya, we constructed the first comprehensive phylogeny of the genus. Four of the genotyped specimens were more than 100 y old. With the exception of the type specimen of Podaxis rugospora, all herbarium specimens were labelled as P. pistillaris or Podaxis sp. However, our data shows that the genus contains at least five well-supported clades with significant inter-clade differences in spore length, width and wall thickness, and fruiting body length, supporting that clades likely represent distinct Podaxis species. Certain clades consistently associate with termites while others appear entirely free-living. Highlights: Six well-defined clades of Podaxis sp. One clade represents Podaxis rugospora . Some clades consistently interact with termites, others are entirely free-living. Fully free-living clades all found in desert regions and form monophyletic group. Old World and New World specimens formed separate groups in the phylogeny.